1993
DOI: 10.1002/hep.1840180432
|View full text |Cite
|
Sign up to set email alerts
|

Ito cell contraction in response to endothelin-1 and substance P

Abstract: The contractile response of cultured Ito cells to endothelin-1 and substance P was examined. Ito cells were obtained from rat liver by perfusion with collagenase, followed by separation through centrifugal elutriation, and were cultured for 24 hr. The area of the Ito cells was measured after treatment with endothelin-1 or substance P at various concentrations in the culture medium. The area of the cells decreased dose dependently after treatment with endothelin-1 or substance P. The area of Ito cells before ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 21 publications
3
70
0
1
Order By: Relevance
“…Recent investigation found that voltage-operated calcium channel (VOCC) plays an important role in the regulation of hepatic stellate cells contractility which is the marked phenotype of activated hepatic stellate cells (Berlin 1995;Bataller et al 1998). Moreover, activated hepatic stellate cells have receptors for a number of vasoconstrictor substances such as endotheline, angiotensin II, vasopressin, thrombin and thromboxan A2 (Pinzani et al 1992;Sakamoto et al 1993;Kawada et al 1993;Bataller et al 1997;Rockey 1997). Therefore, it is likely that the inhibitory effect of tetrandrine on hepatic stellate cells activation, at least in part, through the blocking of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigation found that voltage-operated calcium channel (VOCC) plays an important role in the regulation of hepatic stellate cells contractility which is the marked phenotype of activated hepatic stellate cells (Berlin 1995;Bataller et al 1998). Moreover, activated hepatic stellate cells have receptors for a number of vasoconstrictor substances such as endotheline, angiotensin II, vasopressin, thrombin and thromboxan A2 (Pinzani et al 1992;Sakamoto et al 1993;Kawada et al 1993;Bataller et al 1997;Rockey 1997). Therefore, it is likely that the inhibitory effect of tetrandrine on hepatic stellate cells activation, at least in part, through the blocking of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-1 was selected because of its marked contractile effect for HSCs and its potential pathogenic role in the increased intrahepatic resistance to portal blood flow observed in chronic liver diseases. 6,[9][10][11][12][13][14]39 In the current study, cell contraction was assessed by measuring changes in cell area with a morphometric method. This method was chosen because a large number of studies in different contractile cell types, 40,41 including previous studies from our laboratory in HSCs, 15,26 have used changes in cell area as a reliable tool to evaluate contraction in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Moreover, HSCs have receptors for a large number of vasoconstrictor substances, including endothelin-1, arginine vasopressin, thrombin, thromboxanes, and angiotensin II. 6,8,[11][12][13][14][15] Finally, the stimulation of HSCs in culture with these vasoconstrictor substances is associated with a marked increase in intracellular calcium concentration ([Ca 2ϩ ] i ) and cell contraction, 6,[8][9][10][11][12][13][14][15] suggesting that the contractile function of HSCs may be regulated by the action of vasoconstrictors.In contractile cells, the effects of vasoconstrictor agonists may be attenuated by the action of vasodilators. In fact, the state of contraction/relaxation of contractile cells is dependent on the interaction between vasoconstrictor and vasodilator factors.…”
mentioning
confidence: 99%
“…61 Cultured HSC also contract in response to several vasopressive stimuli including thrombin, angiotensin II, ET, substance P, and eicosanoids. [61][62][63] Additionally, the anatomic location of HSC along the hepatic sinusoids is theoretically ideal to regulate blood flow through contraction and relaxation. 59 HSC in vivo exhibit a quiescent phenotype, but can be activated by stimuli such as inflammatory cytokines, growth factors, and changes in extracellular matrix composition.…”
Section: The Liver Microcirculationmentioning
confidence: 99%